2012
DOI: 10.2139/ssrn.2088196
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and its Role in Household Poverty Reduction: Findings from Pakistan

Abstract: KatsusBrook ISBN : ersity of Ma @bcs.org.uk esponding ersity of Ba i@bath.ac.u ersity of Ma Kobe Unive shi.imai@m ks World Po : 978-1-907 anchester, k author ath, UK uk anchester, ersity, Japa manchester. overty Insti 7247-72-9 UK UK and an .ac.uk itute Micro A Is K J B Creat ofinance reduct Asad K. G ssam Ma Katsushi June 201 BWPI Wo ting and sh ww e and its tion: find Ghalib 1* alki 2 S. Imai 3 2 orking Pa haring know ww.manche role in h dings from 3 aper 173 wledge to h ester.ac.uk/ househol m Pakist help e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Logit, Probit and Tobit are few such models. Here, the more popular model, logit is adopted, where, y (regressand) = 1/0, where '1' signifies the samples from the EG and '0' samples from the CG and x (regressor) = covariates (Chemin 2006;Deininger and Liu 2009a;Deininger and Liu 2009b;Ghalib et al 2012;Islam 2009;Love 2003;Mangala and Chengappa 2008;Owuor 2009;Setboonsarng and Parpiev 2008) where x 1 is age, x 2 educational qualification, x 3 employment status five years back, x 4 marital status, x 5 family type and x 6 is satisfaction levels five years back. These covariates form the profile of clients.…”
Section: Methodology Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Logit, Probit and Tobit are few such models. Here, the more popular model, logit is adopted, where, y (regressand) = 1/0, where '1' signifies the samples from the EG and '0' samples from the CG and x (regressor) = covariates (Chemin 2006;Deininger and Liu 2009a;Deininger and Liu 2009b;Ghalib et al 2012;Islam 2009;Love 2003;Mangala and Chengappa 2008;Owuor 2009;Setboonsarng and Parpiev 2008) where x 1 is age, x 2 educational qualification, x 3 employment status five years back, x 4 marital status, x 5 family type and x 6 is satisfaction levels five years back. These covariates form the profile of clients.…”
Section: Methodology Flowmentioning
confidence: 99%
“…Despite the potency, microfinance suffers from the problem of poor outreach, accessibility and implementation. Sustained efforts are required to bring about real difference to the livelihoods of the poor (Ghalib et al 2012). Numerous studies show that it does not reach the core poor, its use is diverted to uneconomic activity and its contributions are negligible or negative (Sinha 2005).…”
Section: Impact Of Microfinance On Women Empowerment In Matrilineal Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies related to welfarist school focus on the effect of microfinance on the poor people, imply that the effect on the poverty level of the borrowers as the performance of the MFIs. The measures used to reveal the impact of the MFIs on the poor people are the household income, expenditure on healthcare, clothing, water supply and building a quality of a dwelling house (Ghalib, Malki, & Imai, 2011). For the studies related to institutionalist school, the focus is mainly on the efficiency of MFIs to generate profit and to reach more the poor people.…”
Section: Microfinance Institutions Performancementioning
confidence: 99%
“…A plethora of studies in the extant literature have found that microcredit contributes positively to poverty reduction (Ghalib, Malki, & Imai, 2011; Gobezie & Garber, 2007; Imai & Azam, 2010; Imai, Arun, & Annim, 2010; Khandker, 2005). In a related study, it was found that household’s access to microfinance contributed to a long-lasting increase in income by means of increased households’ investments in income-generating activities and possible diversification of resources, accumulation of resources which smoothen household consumption.…”
Section: Introductionmentioning
confidence: 99%